2013
DOI: 10.1080/09585192.2013.778320
|View full text |Cite
|
Sign up to set email alerts
|

Factors helping the HR function gain greater acceptance for its proposals and innovations: evidence from Spain

Abstract: On the basis of the sense-making and sense-giving literature, this study addresses factors helping the HR function gain greater acceptance by employees for its proposals and innovations. Using an original sample of 298 employees from nine firms in Spain, we find that HR department credibility is only one of the factors that influence employees' acceptance. Other essential elements are top management and supervisor support. We also investigate the consequences that differential levels of support from supervisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 45 publications
(69 reference statements)
0
23
0
Order By: Relevance
“…Finally, HR reputation, which is receiving increasing attention ( e.g. Stirpe et al , ), could be an interesting topic to include in different aspects of future implementation research. For example, it would be worth exploring the possible relationships between an HR department's reputation in terms of perceived professional competence and the success of the HR actions described here.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, HR reputation, which is receiving increasing attention ( e.g. Stirpe et al , ), could be an interesting topic to include in different aspects of future implementation research. For example, it would be worth exploring the possible relationships between an HR department's reputation in terms of perceived professional competence and the success of the HR actions described here.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we exclude studies with a perceptual target other than HR practices such as the HR department (e.g. Buyens & De Vos, 2001;Stirpe, Trullen, & Bonache, 2013). Our review focuses on articles appeared in high quality journals, indicated by A Ã and A rankings in the Australian Business Deans Council (ABDC) journal list.…”
Section: Methodsmentioning
confidence: 99%
“…Most HRM outcomes examined at the LTMM level have been individual-level outcomes. For example, research suggests that LTMM support for HRM content is a stronger predictor of employees’ acceptance of that content when compared to TMT support (Stirpe, Trullen, & Bonache, 2013). Furthermore, implementation behaviors (broadly conceptualized as the enactment of HRM content) have been found to influence employee affective commitment (Gilbert et al, 2011b; Shipton, Sanders, Atkinson, & Frenkel, 2016) and the development of psychological contracts (Pak & Kim, 2018).…”
Section: The Roles Of Ltmms In Hrm Researchmentioning
confidence: 99%
“…Although TMTs’ positions distance them from direct implementation of HRM content (i.e., relative to HR managers and LTMMs), four of the TMT studies we reviewed examined the effect of TMTs on the process of translating HRM content into a beneficial outcome. However, consistent with expectations about the role of the TMT, these studies primarily explored how TMTs affect the translation of content into outcomes due to the “big picture” they provide for the organization through values, beliefs, trust, and support (Arthur et al, 2016; Farndale & Kelliher, 2013; Stirpe et al, 2013). More specifically, previous research found that firms’ ability to effectively implement HRM content was affected by things such as value-based HRM beliefs held by TMTs (Arthur et al, 2016) or trust in senior management (Farndale & Kelliher, 2013).…”
Section: The Roles Of Tmts In Hrm Researchmentioning
confidence: 99%